(untitled) (Journal of human and social sciences, 2025)
This research, entitled "From the Dungeons of Prison to the Horizons of Poetry", presents an analytical reading of the poetry collections of the Libyan poet Rashid Al-Zubair Al-Sanousi, written during his imprisonment between 1970 and 1988: From the Cell’s Aperture, Return from the Other World, and Dawn Sweeps Across the Horizon. The study aims to highlight the impact of the prison experience on the poet’s vision and how confinement became a source of creativity and resilience. It employs descriptive and analytical approaches to trace the rhetorical images and symbols expressing suffering and hope such as the walls, night, dawn, and bird—revealing the poet’s journey from pain to liberation. The research concludes that Rashid Al-Zubair’s poetry stands as a human testimony affirming that the word can resist chains, and that freedom is an idea that cannot be imprisoned.